Integrating intrapreneurial self-capital, cultural intelligence, and gender in Chinese international education: pathways to flourishing - Dong, Tianran; Li, Xuetao (Frontiers in Psychology, 2024)
Background: This study investigates the complex interplay between Intrapreneurial Self Capital, Cultural Intelligence, and gender, and their collective influence on the flourishing of Chinese international students in foreign academic settings. As global interconnectivity intensifies, the increasing number of Chinese students seeking education abroad presents a unique opportunity to examine the psychological and sociocultural dynamics of this demographic. Aim: Central to our investigation is the role of Cultural Intelligence, a crucial competency for navigating diverse environments, and Intrapreneurial Self Capital, a composite of psychological resources instrumental in educational and career success. The study also explores the mediating role of Cultural Intelligence in the relationship between Intrapreneurial Self Capital and student flourishing, and examines how gender moderates this dynamic. Method: The research engaged 508 Chinese international students, utilizing a variety of social networks for participant recruitment. The survey, conducted via Qualtrics, focused on a diverse range of students across different educational levels and disciplines. A moderated mediation model was tested to examine the mediation effect of cultural intelligence on the relationship between intrapreneurial self-capital and flourishing, with gender serving as a moderating variable. Results: Our findings reveal significant insights into how Intrapreneurial Self Capital and Cultural Intelligence contribute to the personal and professional development of Chinese international students. Overall, the results suggest that the impact of Intrapreneurial Self Capital on various cognitive qualities (Metacognitive Cultural Intelligence, Cognitive Cultural Intelligence, Motivational Cultural Intelligence and Behavioral Cultural Intelligence) is moderated by gender, highlighting the importance of considering gender differences in this context. Related to the prediction of Flourishing, the direct effect of Intrapreneurial Self Capital on flourishing is notably strong. However, the mediating roles of Metacognitive, Cognitive, and Behavioral aspects of Cultural Intelligence show different levels of influence.The study underscores the need for educational institutions to adopt holistic approaches in fostering student well-being and success, accounting for the nuanced effects of cultural and gender dynamics. These results have significant implications for the development of targeted educational programs and training, aimed at enhancing the international educational experience for students and professionals.